2015
DOI: 10.1111/apa.13040
|View full text |Cite
|
Sign up to set email alerts
|

High rate of sickle cell anaemia in Sub‐Saharan Africa underlines the need to screen all children with severe anaemia for the disease

Abstract: The high prevalence of sickle cell anaemia in children in Sub-Saharan Africa underlines the need for neonatal screening or, if that is not possible, screening of all children with severe anaemia to identify patients with the disease and provide early management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…Previous studies showed that the proportion of sickle cell anemia in the group with negative thick blood smear was significantly higher than that observed in anemic with positive thick smear . These results were confirmed and extended by the findings of a recent study in our midst . Various hypotheses have been advanced to explain this phenomenon such as the invasion of red cells by Plasmodium causes sickling and the destruction of red blood cells by the spleen, impaired parasite egress from dehydrated erythrocytes, the difficulty for the Plasmodium to develop properly under reduced O 2 tension in a sickle red cell, and inhibition of parasite replication by human erythrocyte miRNAs .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Previous studies showed that the proportion of sickle cell anemia in the group with negative thick blood smear was significantly higher than that observed in anemic with positive thick smear . These results were confirmed and extended by the findings of a recent study in our midst . Various hypotheses have been advanced to explain this phenomenon such as the invasion of red cells by Plasmodium causes sickling and the destruction of red blood cells by the spleen, impaired parasite egress from dehydrated erythrocytes, the difficulty for the Plasmodium to develop properly under reduced O 2 tension in a sickle red cell, and inhibition of parasite replication by human erythrocyte miRNAs .…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of SCA is estimated around 40 000 neonates per year . Without access to early diagnosis and adequate management including prevention of infection through the penicillin prophylaxis, pneumococcal vaccination, and health education, from 50% to 90% of these unknown SCD neonates die by the age of 5 years from several complications . An increase in access to early diagnosis is critical for improving these children's survival and quality of life …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Low hemoglobin concentration is diagnosed as anemia, which is caused by more than seventeen different diseases, mainly iron deficiency, hemoglobinopathy, and malaria. [3][4][5][6] The World Health Organization recognizes anemia as a global health problem, affecting a quarter of global population and having prevalence in young children and women. 1,2,[7][8][9] Thus, it is important to measure and monitor hemoglobin in these high-risk subpopulations.…”
Section: Introductionmentioning
confidence: 99%